Efektivitas dan Efisiensi Mulsa Polyethylene terhadap Produksi Bawang Merah (Allium ascalonicum L.) di Lahan Kering: Effectivity and Efficiency of Polyethylene Mulching for Shallot (Allium ascalonicum L.) Production in Dry Land Cultivation - Prathama, Mathias; Santosa, Edi; Susila, Anas Dinurrohman (Indonesian Society for Horticulture / Department of Agronomy and Horticulture, 2025)
Shallots (Allium ascalonicum L.) are an important commodity in Indonesia’s economy, but their growth in dry land areas is often hindered by water limitations and suboptimal environmental conditions. This study aims to evaluate the impact of plastic mulch on the growth and yield of shallots in dry land using a drip irrigation system. The experiment was conducted at the Cikarawang Experimental Field, IPB University, from September to December 2022, using a non-factorial randomized complete block design (RCBD) with plastic mulch and no mulch treatments. The use of plastic mulch tended to reduce plant growth. However, plastic mulch was effective in reducing tuber weight loss, which could potentially increase farmers' income. These findings provide valuable insights for developing sustainable shallot cultivation techniques in dry land areas. Keywords: drip irrigation, dry land, plastic mulch, shallot production, weight loss